2020
DOI: 10.21203/rs.3.rs-42553/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adherence to personal protective equipment use among healthcare workers caring for confirmed COVID-19 and alleged non-COVID-19 patients

Abstract: Adherence observations of health care workers (HCW) revealed deficiencies in the use of recommended personal protective equipment (PPE) among HCW caring in COVID-19 and non-COVID-19 wards during the first period of the SARS-CoV-2 pandemic in a university hospital in Germany. The adherence to wearing surgical face or FFP2-masks and disinfecting hands prior to donning and after doffing the PPE was significantly higher in COVID-19 wards However, there was no total adherence of 100 per cent in COVID-19 wards.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
2

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 3 publications
1
3
0
2
Order By: Relevance
“…[40] Additionally, a lower perceived risk of exposure to SARS-CoV-2 has been associated with decreased adherence to PPE use. [41,42] In accordance with this observation, PPE use among healthcare staff in our study appeared to be less stringent in non-COVID areas. Our study revealed a strong dichotomy between perceived risk and actual risk of exposure to SARS-CoV-2 across healthcare spaces, which appears to be heavily modulated by viral emission rate and timing of disease course.…”
Section: Discussionsupporting
confidence: 87%
“…[40] Additionally, a lower perceived risk of exposure to SARS-CoV-2 has been associated with decreased adherence to PPE use. [41,42] In accordance with this observation, PPE use among healthcare staff in our study appeared to be less stringent in non-COVID areas. Our study revealed a strong dichotomy between perceived risk and actual risk of exposure to SARS-CoV-2 across healthcare spaces, which appears to be heavily modulated by viral emission rate and timing of disease course.…”
Section: Discussionsupporting
confidence: 87%
“…However, we considered this overestimate as the use of all PPE would reduce the risk of infection among healthcare workers during care encounters. Furthermore, existing evidence supports a zero to low healthcare worker infection rates in countries with stringent PPE compliance [ 42 ]. Third, there is a chance that the COVID-19 related mortality in Kenya may be higher than predicted in the model we used as a result of a likely underreporting of COVID-19 deaths in Kenya.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28] In the setting of a pandemic, heightened awareness of personal risk during COVID-19 patient care results in high compliance with PPE and hand hygiene, further decreasing the likelihood of direct patient care exposures. [29][30][31][32] HCPs spend comparatively more time in communal settings, often in con ned and shared spaces such as nursing stations, physician workrooms, breakrooms, and conference rooms. 33,34 Further exacerbating coworker exposure risk is the propensity to work while actively ill, an unintended consequence of strong work ethics that lead to working long hours despite physical discomfort or sickness.…”
Section: Discussionmentioning
confidence: 99%